Analisis Pengendalian Kualitas Voucher Fisik Menggunakan Metode Six Sigma dan 5W+1H di PT XYZ - Raffi Arya Prayoga; Susatyo Nugroho Widyo Pramono (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
The development of the industrial sector has experienced significant acceleration due to the support of advancing technology and creative innovations from various companies. These innovations result from the collective contributions of all levels within a company’s structure. This situation has intensified industrial competition, encouraging companies to continuously innovate in producing products that meet societal needs. Companies capable of creating high-quality products relevant to market demands have a greater chance of surviving and excelling in competition. For instance, between December 2023 and January 2024, a telecommunications company successfully produced 150,077,945 physical vouchers, with an average daily production of 2,543,694 units. During the production process, physical vouchers must meet specific criteria to ensure their quality. Quality control focuses not only on reducing product defect rates but also prioritizes customer satisfaction and loyalty. Six Sigma is one of the methodologies used to increase production process quality by reducing process variance and minimizing the number of defects in products or services. To facilitate the implementation of Six Sigma, the 5W+1H method can serve as a supplementary approach for problem identification and resolution. This technique involves systematically collecting information by answering the questions: What, Where, Who, When, Why, and How.